Analisis Alokasi Dana Dana dalam Pembangunan Desa di Desa Bunut Baok Kecamatan Praya Lombok Tengah: Analysis of Allocation of Funds in Village Development at Bunut Baok Village, Praya District, Central Lombok - Haudiatir Rohmi; Siti Fatimah (LPPM Institut Studi Islam Sunan Doe, 2022)
This study aims to determine the use of Village Fund Allocation (ADD) in village physical development and the impact it has on Village Physical Development in Bunut Baok Village, Praya District, Central Lombok Regency. This study used a qualitative approach, the data collection method used was literature study and field study. The research results were analyzed using a descriptive method, which describes how the use of ADD in village physical development and how the impact of using ADD is in village physical development in Bunut Baok village, Praya sub-district, Central Lombok district. The data validity method used is method triangulation and data source triangulation. The conclusions from this study regarding the use of ADD in village physical development, namely ADD is used based on setting village priority scales that have been approved by the village government based on the results of the Village Deliberation (Musydes). Obstacles in its realization include human resources, land availability and disbursement of funds. The impact felt by the community from the physical development of the village includes easy access to roads, smooth running of the economy and increased income, better environmental management, access to clean water, and smooth farming activities for farmers.